2002
DOI: 10.1111/j.1574-695x.2002.tb00608.x
|View full text |Cite
|
Sign up to set email alerts
|

Neisseria meningitidisserogroup B: laboratory correlates of protection

Abstract: Meningococcal disease in the Western countries is frequently caused by Neisseria meningitidis serogroup B. Major efforts have been made to develop a safe and efficacious vaccine against this serogroup which is suitable for use in infants and young children. To assess the quality of the immune response after vaccination with candidate vaccines, laboratory correlates of protection are needed. For serogroups A and C, serum bactericidal activity (SBA) is a well established predictor for protection, but for serogro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(10 citation statements)
references
References 58 publications
(70 reference statements)
0
10
0
Order By: Relevance
“…Many individual OM and secreted proteins have been investigated for their ability to induce serum bactericidal antibodies (SBA) (18), which is a generally accepted laboratory correlate of protection for serogroup B meningococci (19). Proteomic studies carried out in our laboratory identified the high abundance of a 29-kDa meningococcal MIP protein (the product of gene NMB1567, NEIS1487) in the OM (20).…”
mentioning
confidence: 99%
“…Many individual OM and secreted proteins have been investigated for their ability to induce serum bactericidal antibodies (SBA) (18), which is a generally accepted laboratory correlate of protection for serogroup B meningococci (19). Proteomic studies carried out in our laboratory identified the high abundance of a 29-kDa meningococcal MIP protein (the product of gene NMB1567, NEIS1487) in the OM (20).…”
mentioning
confidence: 99%
“…As MenB is known only to infect humans, suitable animal models do not exist and immune correlates are accepted as an indication of in vivo immune protection for pre-clinical assessment of vaccine candidates [ 22 ]. The SBA is the gold standard correlate of protection required for vaccine licensure.…”
Section: Resultsmentioning
confidence: 99%
“…In certain age groups and demographics, such as the very young and elderly adults or immunocompromised individuals, as well as in countries with a high burden of disease, discordance in antibody levels and functions following immunisation have been reported for pneumococcus [15][16][17], Hib [18][19][20] and meningococcus [21,22]. This discordance is likely due to the generation of non-functioning or weakly binding antibodies, including reduced antibody diversity, defects in isotype switching, and/or a lack of somatic mutation [20,23]. Deficiency in IgM memory B cells is also more commonly seen in the elderly [24].…”
Section: Importance Of Measuring Functional Antibodies Following Vaccinationmentioning
confidence: 99%